Effectiveness of Red Bull’s Model of Football Clubs Sponsorship - Bazanov, Evgenii; Král, Petr, 1979-; Valdová, Viktorie; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
This master's thesis explores the topic of sponsorship. The main goal of this thesis is to determine whether Red Bull’s model of football clubs’ sponsorship is effective from the marketing and financial perspective. The first part of the thesis research sponsorship by conducting a literature review of available information on this subject. The second chapter briefly introduces the company and focuses on the research of two case studies on RB Salzburg and RB Leipzig, which provide the basis for the practical part. The last chapter research the effectiveness of Red Bull's strategy from the marketing and financial perspective.
Vedoucí práce: Petr Král
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses